Functionalized Mouth‐Conformable Interfaces for pH Evaluation of the Oral Cavity. Issue 12 (18th March 2021) - Matzeu, Giusy; Naveh, Gili R. S.; Agarwal, Siddhart; Roshko, Jeffery A.; Ostrovsky‐Snider, Nicholas A.; Napier, Bradley S.; Omenetto, Fiorenzo G.
Abstract: Oral health monitoring is highly desired, especially for in home use, however, current methods are not sensitive enough and technically convoluted for this purpose. This paper presents incorporation of bioactive materials and colorimetric chemical sensors into routinely used oral appliances transforming them into bioresponsive, conformable interfaces. Specifically, endodontic paper points and dental floss can be functionalized to locally sense and monitor pH variations within the oral cavity via color changes. Moreover, edible colorimetric indicators are developed and used to make sensing, edible devices in the form factor of candies that can dynamically and visually respond to acidity changes in saliva. These interfaces would enable early detection of caries (e.g., using dental floss and paper points) providing low‐cost point of care devices that respond in real‐time by detecting pH variations in biological fluids thus bringing monitoring to home settings . Abstract : pH‐responsive biomaterial‐based formulations based on fruit can be tuned to convert inert interfaces such as dental floss and highly absorbent paper points into devices for real‐time localized chemical mapping of the oral cavity. These can be extended to mouth‐conformable interfaces to acquire information on the health status of the user and for the design of point of care diagnostic devices.